Rekrutmen Karyawan di PT. Pegadaian (Persero) Syariah Surabaya Ditinjau dari Perspektif Islam - Hamidah, Nurul; Canggih, Clarashinta (Universitas Negeri Surabaya, 2021)
This research examined how employee recruitment at PT. Pegadaian (Persero) Surabaya Region XII Office from an Islamic perspective. The purpose of this research was to determine whether the implementation of recruitment at PT. Pegadaian (Persero) Surabaya Region XII Office is in accordance with an Islamic perspective. The research method used was descriptive qualitative research using primary data from interviews and secondary data from company annual data and literature studies. Based on the results of research and previous discussions, it showed that the recruitment at PT. Pegadaian (Persero) Regional Office XII Surabaya still has not fully implemented recruitment in accordance with Islamic principles. Therecruitment is still centered at the head office, hence the recruitment in conventional and Islamic units are still carried out in the same system. There are no specific guidelines and criterias for recruitment at Islamic unit in Pegadaian. Furthermore, the company also does not require employees to have basic education in the field of Islamic Economics.